Penguatan Kelembagaan dan Partisipasi Masyarakat pada Pesantren Al-Hilal Bandung melalui Pendekatan Social Marketing - R. Nanang Kuswara; Agustriani Muzayanah; Muhasyim; Yasser Muda Lubis (El Madani : Jurnal Dakwah dan Komunikasi Islam, 2022)
In the midst of the problems of pesantren in this millennial era, which often reaps a less positive image in the community, because of the management and fundraising activities for the construction of pesantren which are taken through the distribution of students or their administrators to the streets and to homes. However, Al-Hilal Islamic Boarding School in Bandung has shown its success by strengthening independent and entrepreneurial programs for its administrators in advancing pesantren. This study uses a social marketing approach through social products and social practices, as well as da'wah bil hal as a pillar of the program for the benefit of the people. The method used, namely focus group discussions (FGD) with leaders, administrators, and students of Al-Hilal Islamic Boarding School equipped with participants and donors from various agencies. The results of the study report that institutional strengthening and community participation are achieved by carrying out social marketing such as managing social products, Ponpes Al-Hilal by publishing the Jabal Qur'an and media, while social practice is the distribution of al-Qur'an waqf. 'an, Waqaf Wells, mobile rice distribution, qurban, LAZIZWAF, and others. For the information media of Al-Hilal Islamic Boarding School through kiai/ustaz lectures, writing works, mass media publications, installing banners, distributing brochures, calendars, bulletins; publication on facebook, whatsapp group, instagram, website; involvement of community participation, alumni, and radio and TV broadcasts. In da'wah bil hal, Al-Hilal Islamic Boarding School holds the principle that Islam is a religion that pays attention to a person's personal relationship with the community and the people who live around him.